Globalization and Income Inequality in Mexico, Indonesia, Nigeria, and Turkey: A Dynamic GMM Approach - Osinubi, Tolulope Temilola; Olomola, Philip Akanni (Asian Journal of Economics and Empirical Research, 2020)
This study examines the effect of globalisation on income inequality in Mexico, Indonesia, Nigeria, and Turkey between 1980 and 2018, using economic, social, political, and overall globalisation as proposed by Dreher., Gaston, and Martens (2008). The study employs a dynamic Generalised Method of Moments. Results show that economic globalisation significantly increases income inequality in Mexico and Turkey, but insignificantly reduces inequality in Indonesia and Nigeria. For social globalisation, inequality responds positively to it in all the MINT countries, except in Turkey. Political globalisation adds to income inequality in Mexico, but reduces inequality in Nigeria and Turkey. In Indonesia, political globalisation exerts insignificant positive effect on inequality. Overall globalisation increases income inequality in all the MINT countries, except in Indonesia. The study, therefore, concludes that the various dimensions of globalisation and overall globalisation are key drivers of income inequality in each of the MINT countries, except in some few cases.